The Effect of Divorce on the Selection of a Friendship Environment in Adolescents - Hanan Sarah Az-Zahra; Jundi Muhammad Fauzan; Wahyunengsih nengsih (Universitas Islam Negeri Imam Bonjol Padang, 2022)
In general, conflicts always occur in married life, but conflicts that often occur can cause one of the factors for divorce. Divorce does not only have an impact on the person concerned (husband and wife) but also involves children, especially those entering their teens because divorce is a burden for each child which can impact on the interest and motivation of learning a child. This is one of the reactions resulting from the divorce of his parents. The reaction of each child to the impact of divorce is greatly influenced by the way parents behave before, during, and after the divorce. The purpose of this study was to determine the attitude of a child or the psychology of each child in choosing a friendship environment either at school or at home. This research method uses a questionnaire method by giving a set of written questions to respondents online. Thus, to overcome this treatment, social workers must strive to achieve the achievement of welfare for children and can provide family counseling services.